Towards Goal-Oriented Recommender- and DataSpace-Driven Volunteering - Schönböck, Johannes; Schwinger, Wieland; Retschitzegger, Werner; Pröll, Birgit; Kapsammer, Elisabeth; Angster, Christoph (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Voluntary engagement is an indispensable cornerstone of Critical Infrastructures (CI) such as civil protection, disaster, crisis and rescue management as well as health and social services. Sustainability of the voluntary sector, however, is massively endangered by profound changes in demography, social structure, and volunteer motives in the sense of individualization and pluralization of society. This paper tackles these key challenges by giving an overview on our digital platform for goal-oriented volunteering across and independently of different non-profit organizations. This platform is intended to be a first step towards synergistically aligning the goals and competencies of volunteers with the activity requirements of CI by proposing first ideals on using recommender and dataspace technologies.